Discrete choice experiment on educating value-based healthcare. Issue 1150 (12th August 2020) - Noben, Cindy Y G; Stammen, Lorette A; Vaassen, Sanne; Haeren, Roel; Stassen, Laurents; van Mook, Walther; Essers, Brigitte
ABSTRACT: Introduction: Identifying costs and values in healthcare interventions as well as the ability to measure and consider costs relative to value for patients are pivotal in clinical decision-making and medical education. This study explores residents' preferences in educating value-based healthcare (VBHC) during postgraduate medical education. Exploring residents' preferences in VBHC education, in order to understand what shapes their choices, might contribute to improved medical residency education and healthcare as a whole. Methods: A discrete choice experiment (DCE) examined which conditions for educating VBHC are preferred by residents. DCE gives more insight into the trade-off's residents make when choosing alternatives, and which conditions for educating VBHC have the most influence on residents' preference. Results: This DCE shows that residents prefer knowledge on both medical practice as well as the process of care—to be educated by an expert on VBHC together with a clinician. They prefer limited protected time to conduct VBHC initiatives (thus while at work) and desire the inclusion of VBHC in formal educational plans. Conclusion: When optimising graduate and postgraduate medical education curricula, these preferences should be considered to create necessary conditions for the facilitation and participation of residents in VBHC education and the set-up of VBHC initiatives.